PEDOMAN DALAM PENANGANAN KANDIDIASIS - Jadeny Sinatra; Jekson Martiar Siahaan (Majalah Ilmiah METHODA, 2018)
Candida species is an important cause of nosocomial infection that lead to death and prolonged hospital stay. The number of immunocompromised patients, at greater risk of fungal infection, treated in intensive care units (ICUs) has increased considerably. The widespread use of invasive monitoring , therapeutic equipment and treatment with broad spectrum antibiotic increases the risk of fungal colonization and infection. An acute awareness of the increasing incidence of Candida as a pathogen and of the associated morbidity and mortality is necessary. Guidelines management of candidiasis by Infectious Disesase Society of America(IDSA) in 2009 previously, was revised. There have been new data pertaining to diagnosis, prevention, and treatment for proven or suspected invasive candidiasis, leading to significant modification in treatment recommendations, which released in 2016. This article provides a summary of the most recent guideline for the management of candidiasis.